2016
DOI: 10.1038/nmat4672
|View full text |Cite
|
Sign up to set email alerts
|

Facet-dependent trapping and dynamics of excess electrons at anatase TiO2 surfaces and aqueous interfaces

Abstract: Excess electrons from intrinsic defects, dopants and photoexcitation play a key role in many of the properties of TiO2. Understanding their behaviour is important for improving the performance of TiO2 in energy-related applications. We focus on anatase, the TiO2 polymorph most relevant in photocatalysis and solar energy conversion. Using first-principles simulations, we investigate the states and dynamics of excess electrons from different donors near the most common anatase (101) and (001) surfaces and aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
274
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(300 citation statements)
references
References 54 publications
14
274
0
4
Order By: Relevance
“…The use of a simple GGA to model reduced anatase is justified by the fact that excess electrons are typically quite delocalized in this material. 46,48 In addition, extensive test calculations including an on-site Hubbard U term (U = 3.3 or 3.9 eV) on the Ti3d states showed trends qualitatively very similar to those obtained with a pure GGA (see the supplementary material for Table S2). We also notice that the GGA-PBE functional does not include van der Waals (vdW) dispersion interactions that have been reported to introduce significant corrections to the computed adsorption energies of metal clusters on TiO 2 in a recent study.…”
Section: Computational Detailssupporting
confidence: 65%
See 1 more Smart Citation
“…The use of a simple GGA to model reduced anatase is justified by the fact that excess electrons are typically quite delocalized in this material. 46,48 In addition, extensive test calculations including an on-site Hubbard U term (U = 3.3 or 3.9 eV) on the Ti3d states showed trends qualitatively very similar to those obtained with a pure GGA (see the supplementary material for Table S2). We also notice that the GGA-PBE functional does not include van der Waals (vdW) dispersion interactions that have been reported to introduce significant corrections to the computed adsorption energies of metal clusters on TiO 2 in a recent study.…”
Section: Computational Detailssupporting
confidence: 65%
“…39 Characteristic features of anatase (101) in comparison to the well-studied rutile TiO 2 (110) surface are that oxygen vacancies reside (well) below the surface 44,45 and excess electrons form poorly localized polaronic states with energy levels in the band gap close to the conduction band (CB) edge. [46][47][48][49] Previous investigations have found that step edges may serve as nucleation sites for the growth of Pt clusters on anatase (101) 50 and 3D Pt structures are preferred on this surface. 51 It was also shown that the interaction of Au clusters with anatase (101) is weaker than that of Pt clusters, 5 and the contributions of van der Waals (vdW) forces can be significant.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, photocatalytic hydrogen production attracts much more attention recently [2][3][4]. Since Fujishima and Honda [5][6][7] discovered hydrogen production from water splitting on TiO 2 for the first time, it is considered as the most promising photocatalyst candidate due to nontoxicity, high stability and low-cost [8][9][10]. Therefore, TiO 2 is widely used in photocatalytic degradation of pollutants, photocatalytic hydrogen production, solar cells, photoelectrochemical devices, and so on [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, based on the Hubbard-corrected DFT + U and first-principles molecular dynamics (FPMD) simulations, facet-dependent trapping and dynamics of excess electrons at anatase TiO 2 surfaces and aqueous interfaces could be achieved. Whereas no electron trapping is observed on the (101) surface in vacuo, an excess electron at the aqueous (101) interface can trigger water dissociation and become trapped into a stable surface Ti 3+ -bridging OH complex [30].…”
Section: The Molecular Dynamics Simulationmentioning
confidence: 99%